Tổng hợp nghiên cứu phức chất của prazeodim với L. Lơxin - Uyển, Nguyễn Trọng; Thiềng, Lê Hữu; Thúy Hằng, Nguyễn Thị; Tuấn, Lê Minh (Vietnam Journal of Chemistry, 2014)
The complex of Prazeodimium with L. Leucine have been isolated on solid state. The complex has the formula H3[Pr(Leu)3(NO3)3]. This complex reveal that L. Leucine acts as a neutral bidentate ligand towards Pr ion at the presence of nitrate ion with utilizing amino nitrogen and carboxyloxygen for bonding.